Effect of Red Blood Cell Aging In Vivo on Their Aggregation Properties In Vitro: Measurements with Laser Tweezers - Petr Ermolinskiy; Andrei Lugovtsov; François Yaya; Kisung Lee; Lars Kaestner; Christian Wagner; Alexander Priezzhev (Applied Sciences, 2020)
Red blood cell (RBC) aggregation highly influences hemorheology and blood microcirculation in the human body. The aggregation properties of RBCs can vary due to numerous factors, including RBC age. The aim of this work was to estimate in vitro the differences in the RBC aggregation properties of different RBC age populations in single-cell experiments using laser tweezers. RBCs from five healthy volunteers were separated into four subpopulations by Percoll density gradient centrifugation. Each subpopulation of the RBC was separately resuspended in autologous plasma or dextran 70 kDa (50 mg/mL). The aggregation force between the single cells was measured with holographic laser tweezers. The obtained data demonstrated an enhancement of RBC aggregation force in doublets with age: the older the cells, the higher the aggregation force. The obtained data revealed the differences between the aggregation and aggregability of RBC in dependence of the RBC in vivo age.